A community for students.
Here's the question you clicked on:
← 55 members online
 0 viewing
anonymous
 4 years ago
y'' + y = tan(t) +e^(3t)  1
I've found the solution, but just want to make sure I'm understanding this right...
I can take the particular solutions of
y'' + y =tan(t)
y''+ y = e^(3t)
y'' + y = 1
and the solution to the homogeneous
y'' + y = 0
and sum them up to get a general solution?
anonymous
 4 years ago
y'' + y = tan(t) +e^(3t)  1 I've found the solution, but just want to make sure I'm understanding this right... I can take the particular solutions of y'' + y =tan(t) y''+ y = e^(3t) y'' + y = 1 and the solution to the homogeneous y'' + y = 0 and sum them up to get a general solution?

This Question is Closed

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0http://tutorial.math.lamar.edu/Classes/DE/UndeterminedCoefficients.aspx Is a good reference for this sort of thing.
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.